2018
DOI: 10.1371/journal.pcbi.1006470
|View full text |Cite
|
Sign up to set email alerts
|

Linking signal detection theory and encoding models to reveal independent neural representations from neuroimaging data

Abstract: Many research questions in visual perception involve determining whether stimulus properties are represented and processed independently. In visual neuroscience, there is great interest in determining whether important object dimensions are represented independently in the brain. For example, theories of face recognition have proposed either completely or partially independent processing of identity and emotional expression. Unfortunately, most previous research has only vaguely defined what is meant by “indep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(61 citation statements)
references
References 92 publications
2
59
0
Order By: Relevance
“…Despite its successes, inverted encoding modeling makes rather strong implicit assumptions about encoding (e.g., homogeneous population codes, normal neural noise) and about the link between neural activity and neuroimaging measures (a linear measurement model with additive normal noise at each measurement, and independent across measurements) [see 14,8]. In addition, the approach has known identifiability problems.…”
Section: Decoding Imprecisionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite its successes, inverted encoding modeling makes rather strong implicit assumptions about encoding (e.g., homogeneous population codes, normal neural noise) and about the link between neural activity and neuroimaging measures (a linear measurement model with additive normal noise at each measurement, and independent across measurements) [see 14,8]. In addition, the approach has known identifiability problems.…”
Section: Decoding Imprecisionmentioning
confidence: 99%
“…For example, face dimensions are often modeled using asymmetric sigmoidal tuning functions [44,5,45,43]. Also, another common assumption for neural channel noise is that it follows a Gaussian distribution [e.g., 6, 7], a common assumption implicit in inverted encoding modeling analyses of neuroimaging data [see 8,14].…”
Section: What About Other Encoding and Decoding Models?mentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical Definitions of Invariance at the Neural Level. In our previous work (Soto et al, 2018), we showed that population encoding models provide a formal theoretical framework within which it is possible to define several forms of invariance and independence of neural representations, and link such theoretical definitions to operational tests performed on neuroimaging or psychophysical data. Here we briefly summarize this framework to facilitate understanding of the invariance tests presented later.…”
Section: Tests Of Invariancementioning
confidence: 99%
“…Despite its wide use, recent theoretical work shows that cross-classification and similar operational tests of invariance can lead to invalid conclusions (Soto et al, 2018). In general, it can be shown that no neuroimaging decoding test can provide evidence in favor of invariance.…”
mentioning
confidence: 99%